2010
DOI: 10.2165/11533060-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Early Worsening after Switch to Aripiprazole

Abstract: Patients with relatively mild illness severity might be more susceptible to early worsening of symptoms when switched to aripiprazole. However, the limitations of the present study, including a small sample size, absence of a control group designed to control for nonspecific factors such as regression to the mean, and implementation of a switching strategy that included only aripiprazole, mean the present findings should be considered with caution and further research is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…Previous studies have indicated that antipsychotic-treated patients with schizophrenia or schizoaffective disorder can be switched to ARIP or ZIP with minimal long-term risk of relapse or symptom worsening (Simpson et al, 2008; Newcomer et al, 2008). However, some patients do not tolerate a medication switch or may experience clinical worsening (Kim et al, 2007; Pae et al, 2010; Takeuchi et al, 2009). In a randomized 12-week study (Newcomer et al, 2008), 8% of the study sample withdrew due to lack of efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated that antipsychotic-treated patients with schizophrenia or schizoaffective disorder can be switched to ARIP or ZIP with minimal long-term risk of relapse or symptom worsening (Simpson et al, 2008; Newcomer et al, 2008). However, some patients do not tolerate a medication switch or may experience clinical worsening (Kim et al, 2007; Pae et al, 2010; Takeuchi et al, 2009). In a randomized 12-week study (Newcomer et al, 2008), 8% of the study sample withdrew due to lack of efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…But on the basis of early case reports, these authors noted that combining aripiprazole with a non-clozapine second-generation antipsychotic might possibly worsen psychosis. Of possible relevance here is a 12-week, randomized, controlled, open-label study [67] designed to identify predictors of worsening in the first 4 weeks after a switch to aripiprazole in people whose schizophrenic illnesses had shown only partial response to previous treatments. The results persuaded the investigators that illness of relatively mild severity may be susceptible to early worsening of symptoms when switched to aripiprazole.…”
Section: Clinical Evidencementioning
confidence: 99%
“…Indeed several ARI trials suggested that a switching method of concomitant ARI initiation and tapering off of the current medication could cause a relapse of psychosis ( Lin et al., 2009 ; Pae et al., 2009 ), although this result was not always confirmed in other trials ( Casey et al., 2003 ; Kim et al., 2009 ). In addition, Pae and colleagues noticed a possible association between psychotic relapse following switching to ARI and DSP ( Pae, 2009 ; Pae et al., 2010 ). We consider that ARI’s agonistic effects may yield excessive dopaminergic effects via the high DRD2 density in patients with DSP, leading to psychotic worsening and switching failure.…”
Section: Introductionmentioning
confidence: 99%